Denture patient’s dental anxiety level during the COVID-19 at RSGM Unpad: cross-sectional study - Syarif, Siti Nur Aulia; Damayanti, lisda; Rosadi, Valentine (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACT Introduction: Dental anxiety is a condition that dentists have faced for a long time. The COVID-19 pandemic was known to have increased dental anxiety in patients, leading to delays in treatment. According to Riskesdas (2018), the rate of tooth loss in Indonesia reached 51.8%. Denture treatment became an option to overcome cases of tooth loss. Dental anxiety was an influential factor in the success of denture treatment. This study aimed to provide an overview of the dental anxiety level of denture patients at RSGM Unpad during the COVID-19 pandemic. Methods: This research was quantitative descriptive research with a cross-sectional design. The sampling technique was simple random sampling. The research instrument was in the form of a questionnaire given online to denture care patients at RSGM Unpad during the COVID-19 pandemic in the period June 2021-June 2022. Result: The number of patients who met the study criteria was 567, and 85 patients were willing to be respondents. The results showed that 92.9% of patients had been vaccinated first in this period. The data showed 56 (65.9%) respondents felt mild anxiety, 23 (27.1%) felt moderate anxiety, and 6 (7%) felt severe anxiety. In the category of moderate and severe anxiety, the number of women was higher than that of men. Conclusion: The majority of dental anxiety experienced by denture care patients at RSGM Unpad was in the mild anxiety category. The causes of anxiety among the patients during the denture treatment process include the use of different materials during the manufacturing process, the fact that the dentures does not fit when used by the patients, and feeling nauseous during molding. The cost factor became the primary reason that discouraged patients from using dentures.KEY WORDS: Dental anxiety, denture, COVID-19Tingkat kecemasan pasien perawatan gigi tiruan saat pandemi COVID-19: Studi cross-sectionalABSTRAKPendahuluan: Kecemasan pasien merupakan kondisi yang sudah dihadapi oleh dokter gigi sejak lama. Terjadinya pandemi COVID-19 diketahui meningkatkan kecemasan pada pasien hingga penundaan perawatan. Menurut Riskesdas (2018) angka kehilangan gigi di Indonesia mencapai 51,8%. Perawatan gigi tiruan menjadi pilihan untuk menangani kasus kehilangan gigi. Kecemasan menjadi faktor yang berpengaruh dalam keberhasilan perawatan gigi tiruan. Studi ini bertujuan untuk melihat tingkat kecemasan pasien perawatan gigi tiruan saat pandemi COVID-19. Metode: Penelitian ini berjenis deskriptif kuantitatif dengan pendekatan cross-sectional. Teknik pengambilan sampel menggunakan purposive sampling. Instrumen penelitian berupa kuesioner yang diberikan secara daring kepada pasien perawatan gigi tiruan RSGM Unpad saat pandemi COVID-19 dalam periode Juni 2021-Juni 2022. Hasil: Sebanyak 92,9% pasien sudah vaksinasi pertama di periode ini. Data menunjukkan 56 (65,9%) responden merasakan kecemasan kategori ringan, 23 (27,1) kategori kecemasan sedang, dan 6(7%) kategori kecemasan berat. Pada kategori kecemasan sedang dan berat lebih banyak diisi oleh perempuan dibanding laki-laki. Simpulan: Kecemasan yang dialami pasien perawatan gigi tiruan mayoritas berada pada kategori kecemasan ringan. Penyebab pasien merasa cemas selama proses perawatan gigi tiruan meliputi, penggunaan bahan yang berbeda-beda saat proses pembuatan, gigi tiruan tidak pas saat digunakan oleh pasien, dan merasa mual saat pencetakan. Faktor biaya menjadi alasan tertinggi yang menghambat pasien untuk menggunakan gigi tiruanKATA KUNCI: Kecemasan dental, gigi tiruan, COVID-19